Herpetofauna Diversity at the Nusa Cendana University - Fadlan Pramatana; Yusratul Aini; Maria M. E. Purnama; Roni Haposan Sipayung; Oki Hidayat (Jurnal Penelitian Pendidikan IPA, 2025)
University campuses are built to carry out the learning process. Therefore, this area has dramatically developed and impacted on the environment and biodiversity. The Nusa Cendana University (Undana) campus area as a habitat for wild animals is included in the built and managed habitat categories. In human-dominated habitats in urban areas such as Undana, it is still possible for animal species to find habitats to find food, shelter, and water sources. This research aims to analyze herpetofauna diversity and update information on preliminary studies of herpetofauna at Nusa Cendana University so that it can be used as primary data for assessing time series. Data was collected using the Visual Encounter Survey combined with the time-constrained search method for three hours from 18.30 to 21.30 WITA at three habitat types (Agricultural, open-area, and built-area habitat). The observation period is divided into two categories: dry and rainy season. Twelve species from eight herpetofauna families, consisting of four amphibians and eight reptiles, were recorded in three habitat types in the Undana campus area. It was recorded that there were six additional herpetofauna species compared to the preliminary study.